2013
DOI: 10.1111/1754-9485.12025
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvements in prostate radiotherapy: Outcomes and impact of comprehensive quality assurance during the TROG 03.04 ‘RADAR’ trial

Abstract: The application of a suite of complementary QA activities allows the quality of trial data to be optimised and quantified, and can provide a catalyst for reforming treatment practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 30 publications
(32 reference statements)
1
50
0
Order By: Relevance
“…Consistency in EBRT dose delivery was assessed via dosimetric audit of centres [3][4][5][6][7] and adherence to trial planning protocol via expert review of each treatment plan [8].…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…Consistency in EBRT dose delivery was assessed via dosimetric audit of centres [3][4][5][6][7] and adherence to trial planning protocol via expert review of each treatment plan [8].…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…Data collection, protocol requirements and QA have been summarised previously [15][16][17][18]. Accrual was from 23 centres in Australia and New Zealand between 2003 and 2008.…”
Section: Patients and Treatmentsmentioning
confidence: 99%
“…-Form-based information on patient clinical factors comprising physical characteristics, comorbidities, medication intake and lifestyle factors captured at randomisation. More complete descriptions of the study protocol and treatment technique specifications can be found elsewhere [18].…”
Section: Patients and Treatmentsmentioning
confidence: 99%
“…It is noteworthy that trial participation is a catalyst for assessing practices and implementing quality improvement studies. Haworth et al estimated that 65% of centres participating in the RADAR SUAS made changes to daily practices to improve set-up accuracy 4,5…”
Section: Introductionmentioning
confidence: 99%